Does Ramadan Harm Infant Health? Evidence from Ethiopia. Issue 4 (1st October 2020) - Lee, Soohyung; Nam, Minhyuk; Jeong, Daeun; Lee, Wonmoon
Abstract : We examine the impact of religious practices on human capital in the context of Ethiopia. We focus on Ramadan, which leads mothers to reduce nutritional intake during the daytime. By exploiting the variation in the extent to which infants were exposed to Ramadan, we estimate the relative disadvantage of Muslim children compared to their non-Muslim counterparts. We find that the exposure to Ramadan in the first trimester has a significant negative effect on the infants' health outcomes, but not on later life outcomes.